Physical activity among South Asian women: a systematic, mixed-methods review - Babakus Whitney S; Thompson Janice L (BMC, 2012)
Abstract Introduction The objective of this systematic mixed-methods review is to assess what is currently known about the levels of physical activity (PA) and sedentary time (ST) and to contextualize these behaviors among South Asian women with an immigrant background. Methods A systematic search of the literature was conducted using combinations of the key words PA, ST, South Asian, and immigrant. A mixed-methods approach was used to analyze and synthesize all evidence, both quantitative and qualitative. Twenty-six quantitative and twelve qualitative studies were identified as meeting the inclusion criteria. Results Studies quantifying PA and ST among South Asian women showed low levels of PA compared with South Asian men and with white European comparison populations. However making valid comparisons between studies was challenging due to a lack of standardized PA measurement. The majority of studies indicated that South Asian women did not meet recommended amounts of PA for health benefits. Few studies assessed ST. Themes emerging from qualitative studies included cultural and structural barriers to PA, faith and education as facilitators, and a lack of understanding of the recommended amounts of PA and its benefits among South Asian women. Conclusions Quantitative and qualitative evidence indicate that South Asian women do not perform the recommended level of PA for health benefits. Both types of studies suffer from limitations due to methods of data collection. More research should be dedicated to standardizing objective PA measurement and to understanding how to utilize the resources of the individuals and communities to increase PA levels and overall health of South Asian women.